OP0092 Remission in Sle: Consensus Findings from a Large International Panel on Definitions of Remission in SLE (DORIS). (9th June 2015) - van Vollenhoven, R.F.; Aranow, C.; Bertsias, G.; Bonfá, E.; Cervera, R.; Costedoat-Chalumeau, N.; Dörner, T.; Houssiau, F.; Lerstrom, K.; Morand, E.; Mosca, M.; Navarra, S.; et al.
Abstract : Background: Treat-to-target recommendations identified "remission" as a target in SLE but recognize that there is no generally accepted definition for remission in this disease. Objectives: To achieve consensus, in a large multi-party international panel, on potential definitions for remission in SLE. Methods: An international expert panel of sixty rheumatologists, nephrologists, dermatologists, clinical immunologists, and patient representatives participated in preparatory exercises, a full-day face-to-face meeting, and follow-up exercises and electronic voting rounds. Results: Eight key statements regarding remission in SLE achieved >90% agreement (table ). There were different viewpoints on the required duration of remission. In addition, the panel expressed strong support (>90%) for the following principles which will guide the further development of remission definitions: I. A definition of remission in SLE will be worded as follows: Remission in SLE is a durable state characterized by [a definition of: absence of symptoms, signs, abnormal labs, (serology)] Ia. Remission-off-therapy requires the patient to be on no other treatment for SLE than maintenance antimalarials. Ib. Remission-on-therapy allows patients to be treated with maintenance antimalarials, stable, low-dose steroids (prednisone ≤5 mg/d), maintenance immunosuppressives and/or stable (maintenance) biologics. II. Assessment of clinical symptoms and signs should be based on a validated index, e.g., clinical-SLEDAI =0, BILAG D/E only, clinical ECLAM =0; supplemented with PhysGA <0.5 (0-3), and with labs included. III. For testing the construct validity of each potential remission definition the most appropriate outcomes (dependent variables) are: Death, Damage, Flares, and HR-QOL measures. Conclusions: The work of this international consensus panel provides a framework for testing individual definitions of remission against longer-term outcomes. Disclosure of Interest: R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, UCB, Consultant for: AbbVie, Biotest, BMS, Crescendo, GSK, Janssen, Lilly, Merck, Pfizer, Roche, UCB, Vertex, C. Aranow: None declared, G. Bertsias: None declared, E. Bonfá: None declared, R. Cervera: None declared, N. Costedoat-Chalumeau: None declared, T. Dörner: None declared, F. Houssiau: None declared, K. Lerstrom: None declared, E. Morand: None declared, M. Mosca: None declared, S. Navarra: None declared, M. Petri: None declared, M. Urowitz: None declared, A. Voskuijl: None declared, A. Voss: None declared, M. Ward: None declared, V. Werth: None declared, M. Schneider: None declared